Laparoscopic Management of a Very Rare Case: Cystic Artery Pseudoaneurysm Secondary to Acute Cholecystitis - Deniz Alis; Sina Ferahman; Süleyman Demiryas; Cesur Samanci; Fethi Emre Ustabasioglu (Case Reports in Surgery)
Pseudoaneurysm of a cystic artery is a rare entity that commonly occurs secondary to biliary procedures. Most of the cases in literature are consisted of ruptured aneurysms and to our knowledge, except our case, there were only 3 cases with unruptured aneurysms, which incidentally were detected by radiological methods. When cystic artery pseudoaneurysm is present with acute cholecystitis, most of the reports in literature suggested open cholecystectomy with the ligation of the cystic artery as a main treatment option. In this paper we present a case of acute cholecystitis with unruptured cystic artery pseudoaneurysm that incidentally was detected by computed tomography (CT). Cystic artery pseudoaneurysm was handled laparoscopically with simultaneous cholecystectomy. Due to high risk of rupture, surgeons have evaded laparoscopic approach to acute cholecystitis, which accompanied cystic artery pseudoaneurysm. However herein, we proved that laparoscopic management of cystic artery pseudoaneurysm with simultaneous cholecystectomy is feasible and reliable method.